The effect of manipulating the expression of the NR2B subunit of the NMDA receptor on learning and memory - Hoon, A (2011)
Overexpression of the NR2B subunit of the NMDA receptor in the forebrain has been shown to improve learning and memory in mice (Tang et al 1999), which provides exciting implications for the enhancement of human cognition. However, it was first essential to establish replicability, and since the Tang et al (1999) study used only male mice we wished to investigate possible sex differences. On the hidden platform watermaze, we found a trend for male NR2BOE mice to learn the task more quickly than male wildtype mice (as observed by Tang et al. 1999), but the opposite trend in female mice; female NR2BOE mice were slower to reach the hidden platform than female wildtype mice. This pattern of results was also observed on the spatial reference Y memory task and open field task (for anxiety), although not on the spatial working memory T maze task (despite a sex difference). However, wildtype and NR2BOE mice performed at similar levels on the novel object recognition task, the spatial novelty preference task, visible platform watermaze and visual discrimination task. A battery of tests considering some species typical behaviours of mice demonstrated that wildtype and NR2BOE mice were comparable on tests of motor ability, strength, co-ordination, anxiety, burrowing and nesting. This suggests that our behavioural results are not due to a general impairment or enhancement of species typical behaviours. We considered the possibility that the difference between the results of Tang et al (1999) and those we observed may be caused by age differences; hence we attempted to replicate our results on the hidden platform watermaze, spatial reference Y maze and open field test in age matched mice. However, the second cohort of NR2BOE mice performed at similar levels to wildtype mice, and at significantly improved levels compared to the mice of the first cohort. We also considered the effects of knocking out the NR2B subunit on learning and memory, and NR1 subunit deletion within the hippocampus. On the spatial working memory T maze, these mouse strains performed similarly to their respective wildtype strains. Similarly, on a two beacon watermaze (with one indicating the platform position), mice lacking the NR2B subunit were able to locate the platform in a similar length of time. To ensure that the null results we had observed in the second cohort were not due to loss of the NR2B protein overexpression in the forebrain, we performed polymerase chain reactions (PCR), quantitative real-time PCR, and Western blots. We ascertained that the transgene was indeed present and that NR2B mRNA and protein levels were elevated in the hippocampi of the NR2BOE mice. In conclusion, it is unclear why the behaviours we observed in the NR2BOE mice are different to those published in the literature. It is possible that they may be due to differences in environmental enrichment, but the cause of the genotype by sex differences observed in the mice of cohort 1 is unclear. Nonetheless, we have advanced our knowledge of the effects of modifications in the levels of the NR2B subunit of the NMDA receptor on learning and behaviour.